PENGARUH METODE PEMBELAJARAN MANDIRI BERSTRUKTUR TERHADAP HASIL BELAJAR SERVIS PANJANG BULUTANGKIS (PADA SISWA SMP NEGERI I SIDAYU) - FANANI, RIO (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract The game of badminton is one of the famous sport in the world . These sports attract different age groups , different levels of skill , both men and women play the sport indoors or outdoors as well as a venue for rekriasi competition . Badminton is also a sport that involves a lot of physical and psychological are so complex that not all children are ready to receive basic technical skills mastery . To get a good mastery of skills , the early feelings of the players should have been given a lesson basic techniques , one technique is to open the game service . Services are divided into four of the long service , short service , service drives and sevis lashes. Therefore, to determine whether there is an independent effect of the use of structured learning methods to learn the results of the long service of badminton is required statistical computer program . To get the conclusions that can be accounted for , it is necessary in the first analysis with the results of the data that have been obtained from computer statistical, and then compared with a table of the T test. This research was conducted In the Junior High School of Students I Sidayu. Analysis using qualitative techniques and techniques deskreptif simple linear regression analysis using a significance level of 5%, the t test used to determine whether there is influence between independent variables and the dependent variable , and the mean test for know how big the effect of independent variables on the dependent variable. The results showed that the test t is greater than t table that is equal to 3.990 > 2.018 , it means that the self- structured learning methods simultaneously affect the learning outcomes of long service has been verified badminton . Mean test shows that the average post - test greater than the pre - test is equal to 71.23 > 59.13 then it can be said that self- structured learning method is quite large influence on the results of long service learning badminton. The conclusion of this study is no significant relationship between the use of structured self-learning method to the learning outcomes of long service badminton Keywords : The Effeck Of A Structured Independent Method, The Serve Outcomes Long Of Badminton